Esthetic Rehabilitation of Anterior Teeth with Laminates Composite Veneers - Dino Re; Gabriele Augusti; Massimo Amato; Giancarlo Riva; Davide Augusti (Hindawi Limited, 2014)
No- or minimal-preparation veneers associated with enamel preservation offer predictable results in esthetic dentistry; indirect additive anterior composite restorations represent a quick, minimally invasive, inexpensive, and repairable option for a smile enhancement treatment plan. Current laboratory techniques associated with a strict clinical protocol satisfy patients' restorative and esthetic needs. The case report presented describes minimal invasive treatment of four upper incisors with laminate nanohybrid resin composite veneers. A step-by-step protocol is proposed for diagnostic evaluation, mock-up fabrication and trial, teeth preparation and impression, and adhesive cementation. The resolution of initial esthetic issues, patient satisfaction, and nice integration of indirect restorations confirmed the success of this anterior dentition rehabilitation.